Hubungan Antara Dukungan Sosial (Suami) Dan Kecemasan Terhadap Baby Blues Pada Ibu Melahirkan Di Kelurahan Ngadirejo Kecamatan Reban Kabupaten Batang - Kiky Novianti; Fitri Awan Arif Firmansyah; Amelia Putri Nirmala (KOLONI, 2024)
This study aims to determine the relationship between husband's social support and anxiety about baby blues syndrome in mothers giving birth in Ngadirejo Village, Reban District, Batang Regency. There are three hypotheses proposed in this research, the first is the major hypothesis which shows that there is a relationship between husband's social support and anxiety regarding baby blues syndrome in mothers giving birth in Ngadirejo Village. The second is minor hypothesis one which shows that there is a negative relationship between husband's social support and baby blues syndrome in mothers giving birth in Ngadirejo Village. Third is the second minor hypothesis which shows that there is a positive relationship between anxiety and baby blues syndrome in mothers giving birth in Ngdirejo Village. The subjects of this research were 60 respondents who were mothers giving birth. This research uses sampling techniques. Data collection used the husband's social support scale, anxiety scale and baby blues scale. The results of this study show that there is a major relationship between husband's social support and anxiety about baby blues with an R count of 0.667 with a significant value of 0.000. These results show that there is a significant relationship between husband's social support and anxiety about baby blues in mothers giving birth. Meanwhile, the results of the minor one test showed an R count of 0.368 with a significance value of 0.004, which indicated that there was a positive relationship between the husband's social support and the mother's baby blues. in the minor test two, it showed an R value of 0.660 with a significance value of 0.000, which indicated that there was a positive relationship between anxiety and baby blues in mothers giving birth in Ngadirejo Village